Prevalence of multidrug-resistant organisms in refugee patients admitted to a German university hospital depending on duration of stay in Germany - Reinheimer, Claudia; Abdollahi, Parisa; Zacharowski, Kai; Meybohm, Patrick; Mutlak, Haitham; Klingebiel, Thomas; Wichelhaus, Thomas A.; Kempf, Volkhard A. J. (German Medical Science GMS Publishing House, 2019)
Background: Refugees have a significant risk of carrying multidrug-resistant organisms (MDRO), including multidrug-resistant gram-negative organisms (MDRGN) and methicillin-resistant (MRSA). Since the duration of MDRGN colonization has been shown to last for several months, we hypothesize that the prevalence of MDRO in refugees gradually declines during their stay in Germany to the level of MDRO prevalence in non-refugee patients. Knowledge about the dynamics of refugees' MDRO prevalence might provide the basis for appropriate infection control measures for refugees in hospitals as well as refugees' MDRO epidemiology in general.Material and methods: MDRO prevalence in 109 refugees admitted to the University Hospital Frankfurt, Germany, were compared to 819 adult controls and 224 pediatric patients admitted to the intensive care unit between June 2016 and May 2017.Results: 41.3% (95% confidence interval=31.9-51.1) of the refugees, 5.7% (4.2-7.6) of the adult controls and 8.9% (5.5-13.5) of the pediatric controls were positive for at least one MDRGN. The highest MDRGN prevalence was found in refugees who recently arrived (≤3 months) in Germany (72.4%; 52.8-87.3). Refugees' MDRGN prevalence declined continuously over time, reaching the adult and pediatric controls' MDRGN prevalence 18 months at the earliest after their arrival in Germany, i.e., 14.9% (1.8-42.8). Conclusion: This study demonstrates that refugees' MDRGN prevalence is declining over time since their arrival in Germany. 18 months after their arrival, refugees' and locals' MDRGN prevalence no longer differs significantly, although the refugees' MDRGN prevalence is still higher. A decline of MRSA prevalence was found 18 months after refugees' arrival. However, MRSA prevalence was still 14%, and thus 8 times higher than that of controls, indicating that precautionary measures continue to be necessary to prevent MRSA transmission.